Construction of Village Autonomy Regulation in Achieving People's Welfare: Critical Review Law Number 6 of 2014 on Villages - Santoso, Lukman (Prodi Hukum Tata Negara Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2021)
This study aims to explore the construction of Village autonomy arrangements to realize people's welfare. As it is understood, the issuance of Law No. 6 of 2014 on Villages has become a new chapter of autonomy regulation in Indonesia, which opens space for villages to be independent and autonomous. This research is juridical-normative research, which includes a descriptive-qualitative type—using secondary data from primary and secondary legal materials. This study applies statute, conceptual and hermeneutic approaches to data analysis. The findings of this study are that in realizing people's welfare, the construction of village autonomy arrangements is based on comprehensive and integrated planning based on each region's potential. So that each region gets benefits and benefits together. The realization of this welfare includes two components: the provision of essential services in the village and the development of the village economy based on local resources' potential.